(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Recycled materials in construction projects are receiving more attention as the demand for sustainable development rises. In order to promote sustainable development, this study aims to evaluate the viability of using recycled materials in urban construction projects from an economic and environmental standpoint. A secondary data strategy was employed in this study to gather and examine already-existing data. Results show that building with recycled materials is a viable strategy for sustainable development. A thorough examination of recycled materials’ physical and chemical characteristics also yields important information about their suitability for construction. The study emphasizes the critical role sustainable urban development plays in advancing the welfare of people, communities, and the environment. The research’s distinctiveness comes in its emphasis on determining if recycled materials may be used in urban construction projects, highlighting the significance of sustainable practices in minimizing our environmental effects while serving the demands of both present and future generations.